2016
DOI: 10.3389/fphys.2016.00545
|View full text |Cite
|
Sign up to set email alerts
|

3,5,3′-Triiodo-L-Thyronine- and 3,5-Diiodo-L-Thyronine- Affected Metabolic Pathways in Liver of LDL Receptor Deficient Mice

Abstract: 3,5,3′-triiodo-L-thyronine (T3) and 3,5-diiodo-L-thyronine (T2), when administered to a model of familial hypercholesterolemia, i.e., low density lipoprotein receptor (LDLr)-knockout (Ldlr−/−) mice fed with a Western type diet (WTD), dramatically reduce circulating total and very low-density lipoprotein/LDL cholesterol with decreased liver apolipoprotein B (ApoB) production. The aim of the study was to highlight putative molecular mechanisms to manage cholesterol levels in the absence of LDLr. A comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…On the other hand, annexins are calcium-dependent phospholipid binding proteins that may regulate various signaling pathways [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. The repressing impact of 3,5-T2 treatment on such a protein seems coherent with the previously reported effect of the iodothyronine on cellular calcium homeostasis [ 73 , 74 ].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, annexins are calcium-dependent phospholipid binding proteins that may regulate various signaling pathways [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. The repressing impact of 3,5-T2 treatment on such a protein seems coherent with the previously reported effect of the iodothyronine on cellular calcium homeostasis [ 73 , 74 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the same animal model used here, an increase in heart rate was observed starting from a dose of 75 μg/100 g BW during a 3-month treatment period (Padron et al, 2014 ). In studies on mice higher doses were used ranging from 250 μg/100 g BW (Jonas et al, 2015 ) to 1,250 μg/100 gBW (Moreno et al, 2016 ; da Silva Teixeira et al, 2017 ). Because the affinity of T2 for TRs is very low but cannot be completely ruled out (Ball et al, 1997 ; Mendoza et al, 2013 ), using high doses and long treatment periods, T3-like TR/TRE-mediated transcriptional effects may come into play, including downregulation of “slow” myosin heavy chain gene transcription in muscle (de Lange et al, 2008 ) and in heart (Edwards et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have chosen to study the anti-lipidemic effects of T2 and T3 using a 1-week period of HFD feeding, leading to lipid accumulation but not to a possible irreversible hepatosteatosis. We chose the dose of T2 [25 μg/100 g body weight (BW)] because in our previous studies, this dose effectively prevented hepatic lipid accumulation without undesirable side effects, and is typically 10-fold lower than the doses used in other studies where cardiac side effects were observed (Padron et al, 2014 ; Jonas et al, 2015 ; Moreno et al, 2016 ). We chose a 10-fold lower dose of T3 (2.5 μg/100 g BW) because it is known that at this dose, T3 activates transcription through TRs/TREs without thyrotoxic effects (Senese et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rat skeletal muscle, T2 has resulted to stimulate mitochondrial uncoupling [126,130]. Interestingly, metabolic and lipid-lowering effects of T2 have also been shown in mice [131][132][133].…”
Section: Nongenomic Regulation Of Mitochondrial Respiratory Chain By ...mentioning
confidence: 98%